Death And Its Effect on the Registration of Property Transfers –Commparative Study- - Ghani, Dr.professor Wasan Qasim; Abd, Abdel Mohsen Raad (The college of law and political science journal, 2024)
In Article (96) of the effective Real Estate Registration Law, many legal barriers that may be related to the real estate or to the owners of real estate rights have been mentioned. In fact, the effect of these legal barriers is varies, some of which prevent the incoming behavior from being registrated on the property. Other, prevent the enforcement of these actions. The act can be registrated in the presence of the barrier, but this behavior does not produce its effects on others. Despite this, death, which can be classified as one of the obstacles related to the owners of real estate rights, it was not considered one of the obstacles that may prevent the registration of real estate actions. Including those transferring ownership that is not considered an argument against all except by the availability of a certain formality specified by law, which is registration in the Real Estate Registration Department.Eventually. The owner of the property is prohibited from using his right. Therefore, the required formality is not completed due to death.